MENDETEKSI OBJEK BERDASARKAN WARNA DENGAN SEGMENTASI WARNA HSV MENGGUNAKAN APLIKASI MATLAB - Adelia Kartika Panggabean; Aldina Syahfaridzah; Nabila Ayu Ardiningih (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2020)
Object recognition using computer vision techniques is a necessary process to detect objects in a 3-dimensional image in order to obtain accurate results. By utilizing the color segmentation method with HSV color, it will produce an image segment object in the form of a blob so that it can be detected by the computer. Based on the test results, the color sample will produce a value that will be the reference for the filter range in the segmentation process. In the process, it will be known how many objects were detected according to the specified color.